Conceptual Analysis of Education Role in Economics: The Human Capital Theory - Galiakberova, Alfinur Azatovna (Journal of History Culture and Art Research, 2019)
The article deals with theoretical issues of building the human potential that is necessary for economic growth and social development. There are some theories, differently interpreting the role of education and the issue of demand for individuals in the labor market. In recent decades, the human capital theory has come to the fore. According to it, human capital rises due to a number of reasons, but the key factor is the educational level of the individual. There have been analyzed views of prominent economists who laid the foundations of this theory. Their undoubted merit is that since then there has been a huge increase in investment into a human being all over the world, since people began to be considered as an important factor in development, as an investment into tangible assets. There also have been considered the evolution of this theory, which was gradually freed from the elements of simplified economic determinism. It is indicated that in modern Russian realities further expansion of higher education does not always lead to an increase in employees’ income. Along with the arguments of the supporters of this theory, the article contains the arguments of its critics. Owing to discussions, the theory is developing and getting flexible. The concept of “human capital” is expanding and now it includes a variety of personality abilities that make it possible for a person to solve economic and many other problems. Therefore, the theory is gradually becoming the subject of broad multidisciplinary research.